Histotripsy ablation for the treatment of feline injection site sarcomas: a first-in-cat in vivo feasibility study - Lauren Ruger; Ester Yang; Sheryl Coutermarsh-Ott; Elliana Vickers; Jessica Gannon; Marlie Nightengale; Andy Hsueh; Brittany Ciepluch; Nikolaos Dervisis; Eli Vlaisavljevich; Shawna Klahn (International Journal of Hyperthermia, 2023)
AbstractPurpose Feline soft tissue sarcoma (STS) and injection site sarcoma (fISS) are rapidly growing tumors with low metastatic potential, but locally aggressive behavior. Histotripsy is a non-invasive focused ultrasound therapy using controlled acoustic cavitation to mechanically disintegrate tissue. In this study, we investigated the in vivo safety and feasibility of histotripsy to treat fISS using a custom 1 MHz transducer.Materials and Methods Three cats with naturally-occurring STS were treated with histotripsy before surgical removal of the tumor 3 to 6 days later. Gross and histological analyses were used to characterize the ablation efficacy of the treatment, and routine immunohistochemistry and batched cytokine analysis were used to investigate the acute immunological effects of histotripsy.Results Results showed that histotripsy ablation was achievable and well-tolerated in all three cats. Precise cavitation bubble clouds were generated in all patients, and hematoxylin & eosin stained tissues revealed ablative damage in targeted regions. Immunohistochemical results identified an increase in IBA-1 positive cells in treated tissues, and no significant changes in cytokine concentrations were identified post-treatment.Conclusions Overall, the results of this study demonstrate the safety and feasibility of histotripsy to target and ablate superficial feline STS and fISS tumors and guide the clinical development of histotripsy devices for this application.